React Native for Android: Cross-Platform Mobile Application Development - Dekkati, Sreekanth; Lal, Karu; Desamsetti, Harshith (Global Disclosure of Economics and Business, 2019)
React Native has been embraced by many companies, and some of the most well-known applications in the world, including Facebook, Uber, and Pinterest, are among those that have done so. Why is it so widespread? What does it mean to react natively? It will likely attribute a significant portion of its success to the company's ability to utilize a single codebase compatible with several platforms. The use of React Native is continually gaining more widespread support. While developing mobile applications, using React Native can have positive and negative effects, and this article will help us grasp both aspects. This study will provide all the necessary information before we use React Native in one of our applications. With this knowledge, we can determine if react native is the appropriate choice for our next project.